Covid-19 and The Effectiveness of Monetary Policy Quantitative Easing Indonesia - Dudi Duta Akbar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The basis for this research is to examine the impact of the Covid-19 pandemic on Indonesian financial markets and the dynamics of monetary policy. Focus on monetary policy conducted by Bank Indonesia regarding Quantitative Easing . The study was conducted using balance sheet information from a sample of 38 private foreign exchange banks in Indonesia to then find out whether policies have an effect on